SOME NOTES ON THE SHALLOW STRUCTURE HYPOTHESIS - Clahsen, Harald; Felser, Claudia (Studies in second language acquisition, 2018)
Since the Shallow Structure Hypothesis (SSH) was first put forward in 2006, it has inspired a growing body of research on grammatical processing in nonnative (L2) speakers. More than 10 years later, we think it is time for the SSH to be reconsidered in the light of new empirical findings and current theoretical assumptions about human language processing. The purpose of our critical commentary is twofold: to clarify some issues regarding the SSH and to sketch possible ways in which this hypothesis might be refined and improved to better account for L1 and L2 speakers’ performance patterns.